2023
DOI: 10.3389/fnut.2022.1092059
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index: A potential biomarker for predicting the prognosis of decompensated liver cirrhosis

Abstract: BackgroundPrognostic nutritional index (PNI) is an independent predictor of the prognosis of various diseases. However, the prognosis value of PNI in patients with decompensated liver cirrhosis (DLC) remains unknown. The study aimed to investigate the prognostic significance of PNI in patients with DLC.MethodsA total of 214 eligible patients were enrolled in the study’s development cohort between January 2018 and March 2021. The clinical primary study endpoints were mortality at 3 and 6 months. Receiver operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…In recent years, the utility of PNI as a prognostic indicator for overall survival has been validated in patients with cancer, cardiovascular disease, decompensated liver cirrhosis, diabetic nephropathy and those undergoing dialysis [22][23][24][25]. Consistent with previous studies, our RCS model revealed a linear-like relationship between PNI and all-cause mortality of hemodialysis patients, with a smooth curve that closely resembled a straight line, indicating a strong prognostic value of PNI.…”
Section: Discussionsupporting
confidence: 84%
“…In recent years, the utility of PNI as a prognostic indicator for overall survival has been validated in patients with cancer, cardiovascular disease, decompensated liver cirrhosis, diabetic nephropathy and those undergoing dialysis [22][23][24][25]. Consistent with previous studies, our RCS model revealed a linear-like relationship between PNI and all-cause mortality of hemodialysis patients, with a smooth curve that closely resembled a straight line, indicating a strong prognostic value of PNI.…”
Section: Discussionsupporting
confidence: 84%
“…Currently, there are many challenges with tools used to assess the nutritional status of CLD patients. PNI is a simple, objective indicator of inflammation and nutritional status, calculated from only serum albumin and lymphocyte counts [ 15 , 16 , 31 ]. In recent studies, PNI has also been significantly correlated with prognosis and nutritional status in a variety of diseases [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…PNI is a simple, objective indicator of inflammation and nutritional status, calculated from only serum albumin and lymphocyte counts [ 15 , 16 , 31 ]. In recent studies, PNI has also been significantly correlated with prognosis and nutritional status in a variety of diseases [ 31 ]. PNI may be useful in the nutritional assessment of patients with CLD.…”
Section: Discussionmentioning
confidence: 99%
“…The PNI is a systemic immunonutrition index based on peripheral lymphocyte counts and serum albumin levels [ 21 ], which provides a reliable and comprehensive assessment of the nutritional and inflammatory status of patients [ 22–23 ]. In addition, the PNI has been shown to be a prognostic biomarker for all-cause mortality in patients with decompensated liver cirrhosis [ 24 ], type-2 diabetes [ 25 ] and various cancers [ 26–29 ]. The PNI is also a predictor of the progression of diabetic nephropathy, and PNI is inversely associated with the incidence of end-stage nephropathy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%